Destination Risk Profile, Message Framing, and Tourist Visiting Intention in the New Life Era - Putu Saroyini Piartrini; Komang Ardana; PA Andiena Nindya Putri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to examine the effect of the level of destination risk on the intention to visit Bali by considering attitudes towards tourist risk and the framing of destination marketing communication messages in the target market. In the context of recovering tourism activities, this study provides input for tourism destination managers regarding the perception of destination risk from a tourist perspective as input in formulating a destination marketing strategy by considering the effect of destination risk perception, and the attitude of target tourists on the risk of travel to their intention to visit or travel. after the policy of limiting community activities, especially the perception of risk on tourist travel activities. The research method used a quasi-experimental design. Starting with measuring the risk perception of a Bali destination, then measuring the intention of tourist visits in groups that have a high-risk perception and a low-risk perception by considering the Bali destination advertising message framing strategy. Data was collected in cities that are the target market for Indonesian tourists, namely Jakarta, Bandung, Yogya, Solo, Semarang and Surabaya, Medan, and Manado. The types of data in this study are quantitative data and qualitative data. The findings of this study recommend to the managers of Bali tourist destinations that destination communication is managed carefully. Management of messages related to Bali destinations to consider the strategy of framing messages communicated to potential markets to manage the perceived risk of visiting the destination. The results of data analysis concluded that: 1) Perception of Bali destination affects the intention to visit Bali. 2) Destination-related message framing strategies affect the intention to visit Bali.